ChemInform Abstract: Reaction Dynamics of Molecular Hydrogen on Silicon Surfaces: Importance of Lattice Degrees of Freedom. Issue 35 (2nd September 2014) - Duerr, Michael; Hoefer, Ulrich
Abstract Review: 76 refs.